2009
DOI: 10.1186/1478-7547-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Can economic evaluation in telemedicine be trusted? A systematic review of the literature

Abstract: BackgroundTelemedicine has been advocated as an effective means to provide health care services over a distance. Systematic information on costs and consequences has been called for to support decision-making in this field. This paper provides a review of the quality, validity and generalisability of economic evaluations in telemedicine.MethodsA systematic literature search in all relevant databases was conducted and forms the basis for addressing these issues. Only articles published in peer-reviewed journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 60 publications
2
84
0
4
Order By: Relevance
“…23 These findings are echoed in a previous telemedicine reviews, which have criticised economic evaluations for failing to take into account important costs, neglecting associated indirect costs and not using standard economic evaluation techniques. 24,25 While evidence demonstrating CBA in telephone coaching is limited, a range of other positive outcomes were reported. These outcomes varied across the studies reviewed, although most reported physical benefits, mental health improvements, self-reported health perceptions and self-care regimen compliance.…”
Section: Discussionmentioning
confidence: 96%
“…23 These findings are echoed in a previous telemedicine reviews, which have criticised economic evaluations for failing to take into account important costs, neglecting associated indirect costs and not using standard economic evaluation techniques. 24,25 While evidence demonstrating CBA in telephone coaching is limited, a range of other positive outcomes were reported. These outcomes varied across the studies reviewed, although most reported physical benefits, mental health improvements, self-reported health perceptions and self-care regimen compliance.…”
Section: Discussionmentioning
confidence: 96%
“…27,34 However, despite the common assumption that telemedicine is cost reducing, at this point the accumulation of data on cost lags well behind that of data supporting clinical efficacy. 28,35,36 There is currently a lack of coherent methodology for the cost evaluation of services delivered via telemedicine. Researchers have noted the need for studies that measure quantifiable clinical and cost outcomes, including measures of efficacy, efficiency, and opportunity cost, 37 when conducting studies to determine if the potential benefits outweigh the costs of providing services via telemedicine.…”
mentioning
confidence: 99%
“…Significant research has been performed, but more is required as the quality of research and value of the resulting solutions have been frequently questioned, particularly for economic studies. [7][8][9][10][11] However, the sheer volume and generally positive impact of the telehealth literature must hold some weight. The need for a "realistic review" to explain what works, for whom, and in what circumstances seems urgent.…”
Section: Introductionmentioning
confidence: 99%